2017
DOI: 10.1111/dme.13372
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms are persistent in Type 2 diabetes: risk factors and outcomes of 5‐year depression trajectories using latent class growth analysis

Abstract: A subset of individuals with Type 2 diabetes is at risk of depression symptoms that remain elevated over time. Younger, overweight individuals with a history of depression may benefit from early and intensive depression management and ongoing follow-up as part of routine Type 2 diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 30 publications
3
31
0
1
Order By: Relevance
“…In addition, the present study participants reported remote depression histories at follow-up and recall bias is also known to lead to underestimates of lifetime depression history [26]. The present results are consistent with studies demonstrating that depression in Type 2 diabetes is prone to become chronic or recurrent [27], with depressive symptoms remaining persistently elevated for up to 5 years [28]. We conducted sub-analyses based on the presence or absence of baseline depressive symptoms in order to investigate whether there were additional risk factors for study participants with depression at both times.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the present study participants reported remote depression histories at follow-up and recall bias is also known to lead to underestimates of lifetime depression history [26]. The present results are consistent with studies demonstrating that depression in Type 2 diabetes is prone to become chronic or recurrent [27], with depressive symptoms remaining persistently elevated for up to 5 years [28]. We conducted sub-analyses based on the presence or absence of baseline depressive symptoms in order to investigate whether there were additional risk factors for study participants with depression at both times.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of depression in patients with diabetes has been widely reported (Katon, 2008). Rates of depression are significantly enhanced in diabetic patients: near 20-30% of diabetes patients suffered from clinically relevant depressive disorders (Fiore et al, 2015), and the risk of depression remains elevated over time in some type 2 diabetes patients (Whitworth et al, 2017). The metabolic dysfunction of obesity contributes to the development of depression (Carmo-Silva and Cavadas, 2017), and the interaction between depressive symptoms and metabolic dysfunction may be a risk factor for type 2 diabetes (Schmitz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There was a high prevalence in social phobia, panic disorders or agoraphobia, psychological distress, OCD and GAD in type 1 patients with diabetes compared with type 2 [14][15][16]21,31,32]. Type 1 population with diabetes appears since childhood and it possible that increase in glucose and indicated as predictive of high anxiety [18,[23][24][25][26][27][28][29][30]. Also, they must have frequent self-monitoring and reasonable application of injectable insulin by the glucose level may contribute to this higher prevalence of anxiety present in type 1 patients [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher correlation in lifetime major depression disorder with current depression symptom (B=3.16, p<0.001). The presence of lifetime GAD was associated with the severe current depression, as well, when patient had high hyperglycaemical (p<0.001) [27].…”
Section: Prospective Observational Studies [6]mentioning
confidence: 92%
See 1 more Smart Citation